The A to Z of arts management : reflections on theory and reality - Tonks, Ann (Routledge, 2020)
"The A to Z of Arts Management, Second Edition covers 97 topics about the management of arts and cultural organisations. Each section offers a theoretical and conceptual introduction to the topic, as well as storytelling and reflections about the meaning and application of such theories in the real world. Drawing on the author's past as a manager running media and performing arts companies and her present as a consultant helping boards and managers, this book covers a wide range of topics, from leadership, motivation and cultural policy to passion, coffee and laughter. This second edition includes even more coverage and stories about the challenges of arts management, and new topics such as harassment, philanthropy and venues. Written for arts managers, students and board members anywhere in the world, The A to Z of Arts Management provides information about research and academic best practice in arts management alongside stories about the reality of working in the arts and cultural industries"- Resumé vydavatel